Social Licence Comes to Greenland’s Mining Sector: Will Communities be Empowered? - Bowles, Paul; MacPhail, Fiona (The Arctic Institute of North America, 2022)
The social licence to operate is a concept that has been applied to the mining sector internationally for the past two decades. In 2017, it was raised by a number of actors as a way to reduce controversy over mining projects in Greenland. In this paper, we analyse why the concept of social licence appeared, and the legitimacy problems that it was intended to resolve despite numerous changes to Greenland’s mining approval processes. We argue that the concept was introduced primarily as a way of seeking to enhance the voices and agency of local communities in resource governance. We further ask whether, on the basis of Canadian experience where social licence has been used for much longer in natural resource governance discourse, introducing the concept into Greenland will likely lead to an empowerment of communities. We argue that the Canadian experience in this regard shows that the outcome is complex, that community empowerment can take different forms or may not occur at all. Such complexity is also likely in Greenland. Le permis social d’exploitation est un concept qui a cours dans le secteur minier international depuis deux décennies. En 2017, ce permis social a été soulevé par un certain nombre d’acteurs comme manière d’atténuer la controverse entourant les projets miniers du Groenland. Dans cet article, nous analysons ce qui a donné le jour au permis social d’exploitation et les problèmes de légitimité que ces permis étaient censés résoudre malgré les nombreux changements apportés aux processus d’approbation de l’exploitation minière au Groenland. Nous soutenons que le concept a été principalement adopté pour tenter d’améliorer la voix et l’instrumentalité des communautés locales en matière de gouvernance des ressources. Par ailleurs, nous tâchons de déterminer, en fonction de l’expérience canadienne où le permis social d’exploitation est utilisé depuis beaucoup plus longtemps dans le discours de la gouvernance des ressources naturelles, si l’adoption de ce concept au Groenland engendrera ...